SERIAL ESTIMATION OF SERUM MAGNESIUM, CALCIUM, SODIUM AND POTASSIUM LEVELS IN MYOCARDIAL INFARCTION - DR. P.KIRANMAI M.D (International Journal of Pharma and Bio Sciences, 2013)
Acute Myocardial Infarction (AMI) is a major public health problem. Fifty percent of deaths associated with AMI are attributable to arrythmias which result due to myocardial ionic imbalance of cations Na+,Mg+2, Ca+2, and K+. Present study aims to find serial change in cation levels in MI cases and their relationship to arrythmias. Methods: Seventy five patients admitted to Intensive Coronary Care Unit (ICCU) with provisional diagnosis of acute myocardial infarction constituted the study group. They were studied serially on 1st, 3rd and 7th day of infarction. Thirty subjects without any heart disease and renal pathology, who were seen in the outpatient departments and healthy volunteers were taken as controls. S.Mg+2, Ca+2, Na+ and K+ were measured in controls and study group and compared. Results: Mean values of all the cations were lowered on 1st day of MI in study group compared to controls (p<0.01). A strong association between low Mg+2 and low K+ levels in MI cases and development of arrythmias is observed (p<0.001). Conclusions: Serial estimation of S.Mg+2 can be used as a diagnostic test for MI. Estimation of S.Mg+2 and S.K+ can be used as prognostic markers in MI.